Nanostructure Zn–Cu co-doped CdS chalcogenide electrodes for opto-electric-power and H2 generation. (5th January 2017) - Pareek, Alka; Thotakuri, Rambabu; Dom, Rekha; Kim, Hyun Gyu; Borse, Pramod H.
Abstract: An efficient photoanode of Zn–Cu: doped nanostructure CdS film has been fabricated by a very simple and commercially usable chemical bath deposition methodology. The electrodes of various sizes were deposited, those ranged from 10 × 10 mm to 100 × 100 mm. Physico-chemical property of the film is investigated in-depth for the photo-electrochemical (PEC) hydrogen production and electric-power generation application. Especially, we studied the effect of Zn and Cu co -doping in the hexagonal CdS-lattice w.r.t. the structural, optical and PEC properties of the nanostructure film. Zn-doping induces an increase in the absorption of visible light photons. The doping enhances the photocurrent by twice as to the undoped, and generates a net photocurrent of ∼817 μA/cm 2, at a very low applied potential of 0.1 V/SCE, in contrast to 366 μA/cm 2 of its undoped counterpart. Electrochemical impedance spectroscopy demonstrated that the reduced e–h recombination is responsible for the superior performance of the electrodes. PEC cell fabricated by these electrodes showed a maximum hydrogen generation rate of ∼6.74 μmol/h as compared to 0.58 μmol/h from undoped counterpart; Further a photo to electric-power conversion efficiency of ∼0.16% has been achieved even at low biasing potential of 0.1 V /SCE under AM 1.5 solar simulated illumination. Undoped, Zn doped and Cu co -doped films are highly useful for dual applications of " solar power-generation " and " solar hydrogen-generation ", revealing that the Zn doped PEC solar cell is most efficient system for the hydrogen generation even at a very low voltage bias of 0.1 V/SCE. Graphical abstract: Highlights: Deposition of Zn and Cu co -doped nanostructure films by chemical bath deposition. Structural and optical properties are revealed. Doping and Co -doping enhances the photocurrent by more than twice in CdS. Zn doped CdS shows improved power conversion and STH efficiency of 0.50% and 0.16% respectively. Low cost method for fabrication of dual purpose PEC cell.